An Exploratory Study on Support to Small and Medium Enterprises: Evidence from Seda Business Advisors, South Africa - Rankhumise EM; Muzanenhamo A (Economics and Entrepreneurship: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Introduction: This paper/chapter aims to investigate the effectiveness of support provided by a selected government agency. The contribution made by SMEs towards economic development is enormous. This is a result that they contribute to the creation of employment and the GDP of the country. Due to the contribution made by this sector, the government has prioritised its development and support to ensure success. As a result of the government’s intention to support the promotion of small businesses, several government agencies are making efforts to support SMEs to enable them to grow and be sustainable. Methodology: In this study, an exploratory research design was chosen to have a better understanding of the existing research problem without providing conclusive results. The study followed a qualitative research method, and data was collected through a semi-structured interview with ten business advisors. In analysing data, Tesch’s data reduction of open coding was used. Results: The findings revealed that participants believed that efforts are being taken by the government to provide valuable support to small businesses. The participants agree that government support is important in promoting entrepreneurial development. Notably, the participants further alluded that they are providing an array of support services to SMEs to ensure that they flourish in their business endeavours. It further emerged that the participants believed that they were not doing their best regarding the advertisement of their offices and the services that they provide. Conclusion and Recommendations: The government agency is supporting the SMEs, though not on the scale they expected due to a lack of awareness of their services. It can be concluded that the support provided by government agencies is positively acknowledged. Due to the challenges of access to finance and the market, SEDA should strengthen its support in this regard.